2005
DOI: 10.1007/s00441-005-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the sodium channel Nav1.2 in chemically identified myenteric neurons in the guinea pig

Abstract: Our purpose was to identify Na(v)1.2-expressing myenteric neurons of the small and large intestine of the guinea pig by using antibodies directed against Na(v)1.2 and selected neurochemical markers. Na(v)1.2-like immunoreactivity (-li) co-localized with immunoreactivity for choline acetyltransferase in all regions, representing 45%-67% of Na(v)1.2-positive neurons. Na(v)1.2-li co-localized with immunoreactivity for the neural form of nitric oxide synthase more frequently in the colon (20% of neurons exhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The in situ hybridization method fulfils the criterion of high selectivity, because specific antisense and sense oligonucleotide probes were designed from the coding region of the guinea pig cDNA sequences of the Na v 1.1, Na v 1.2, Na v 1.3, Na v 1.6, and Na v 1.7 α subunits. Unexpectedly, we found that, among the mRNAs of these five α subunits, only the Na v 1.3 and Na v 1.7 mRNAs could be detected in the ENS, although we could replicate the immunolabeling of ENS structures for Na v 1.2, Na v 1.3, and Na v 1.6 described by Bartoo et al (2005,2006a,b) with the antibodies they used. By using converging immunohistochemistry, Western blot, and molecular biology approaches, we determined the origin of the discrepancies between the immunohistochemistry and the in situ hybridization results and confirmed the validity of the in situ hybridization experiment results.…”
mentioning
confidence: 39%
See 3 more Smart Citations
“…The in situ hybridization method fulfils the criterion of high selectivity, because specific antisense and sense oligonucleotide probes were designed from the coding region of the guinea pig cDNA sequences of the Na v 1.1, Na v 1.2, Na v 1.3, Na v 1.6, and Na v 1.7 α subunits. Unexpectedly, we found that, among the mRNAs of these five α subunits, only the Na v 1.3 and Na v 1.7 mRNAs could be detected in the ENS, although we could replicate the immunolabeling of ENS structures for Na v 1.2, Na v 1.3, and Na v 1.6 described by Bartoo et al (2005,2006a,b) with the antibodies they used. By using converging immunohistochemistry, Western blot, and molecular biology approaches, we determined the origin of the discrepancies between the immunohistochemistry and the in situ hybridization results and confirmed the validity of the in situ hybridization experiment results.…”
mentioning
confidence: 39%
“…As indicated above, the Na v 1.2 α subunit has been previously immunolabeled using a polyclonal Ab raised against the 467–485 rat Na v 1.2 sequence (Westenbroek et al,1989; Planells‐Cases et al,2000; Bartoo et al,2005,2006a,b; Osorio et al,2005). Thirteen of the nineteen amino acids of this rat sequence are conserved in both the rat and the guinea pig Na v 1.3 orthologues.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations